An Icelandic Mystery? The Occurrence of Purple Bones in Arctic Foxes - Julian Egon Ohl 1990- (2020)
In 2007, the first Icelandic Arctic fox with purple mandibles was discovered. The discolouration reappeared in 2013 and each subsequent year until and including 2018. This thesis is the first investigation of purple mandibles in Icelandic Arctic foxes. Hunter or latter mandible handling and storage were not related to the discolouration. Discolouration colour and intensity were quantified creating a baseline for identification of purple mandibles. Finally, spatial, and temporal distribution of the discolouration were mapped. Initially, the discolouration was quantified using digital photography for colourimetry. The dimensions a* and Gnormalized from the L*a*b* and sRGB colour spaces were found to be the most suitable measures of discolouration. Foxes with purple bones derive most of their diet from the ocean. Most purple bones originated from the Westfjords of Iceland; predominantly in the Súðavíkurhreppur municipality. The definitive cause was not investigated. Nevertheless, three potential causes of discolouration are postulated and discussed: (1) environmental pollutants, (2) alga pigments from the Drangajökull glacier that enter the food chain, and (3) sea mussel shell pigments. Further, this thesis suggests mussels would be the vector for transmission to foxes. As filter-feeders mussels accumulate pollutants and/or natural pigments from the environment and they are a secondary food source of Arctic foxes. The Arctic fox is a top predator, which means bioaccumulation of pollutants will be exacerbated and effects manifested earlier in this species. The abrupt occurrence, disappearance, reoccurrence, and location of purple mandibles suggests possible recent sporadic environmental events of variable duration occurring in the Westfjords.